Library resilience and leadership in a global crisis - Shaghaei, Najmeh; Knowles, Claire; Morley, Fiona; Eveleigh, Alexandra; Casaldàliga, Núria; Nolin, Emma; Tatai, Andrea; Cohen, Marc; Pronk, Martine; Ghesquière, Elke (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2022)
Research Libraries, like other organisations during the COVID-19 pandemic, have been facing difficult choices concerning which services to offer, whilst minimising risk to their staff, communities, and users. As the post COVID-19 era beckons, library leaders are urged to adapt flexible strategic plans that apply to every facet of library operation to ensure the organisations remain both safe and resilient in the future. This paper discusses leadership skills and practical techniques that can be applied to help build resilient libraries and deliver positive new change in the post-COVID-19 recovery period. Our findings indicate that leaders need to find ways to realign library ambitions to this uncertain new operating environment. The focus should be directed to digitisation and supporting systems, as well as on sustainability and transformative services. These are a must for the future of libraries.